Writing women's worlds : Bedouin stories - Abu-Lughod, Lila. (Berkeley : University of California Press, 1993)
Lila Abu-Lughod draws on anthropological and feminist insights to construct a critical ethnography of a small Awlad 'Ali Bedouin community in Egypt. She explores how the telling of stories of everyday life challenges the power of anthropological theory to render adequately the lives of others and the way feminist theory appropriates Third World women.
Hc2022A
Keywords: avioliitto; beduiinit; etniset ryhmät; islam; moniavioisuus; naisen asema; naiskulttuuri; patrilineaalinen polveutuminen; sukulaisuus; äktenskap; beduiner; etniska grupper; islam; månggifte; kvinnans ställning; kvinnokultur; patrilinjär härstamning; släktskap; Afrikka; Egypti; Afrika; Egypten